History of hydraulics and fluid mechanics at Colorado State University - Julien, Pierre Y., author; Meroney, Robert N., author; Colorado State University, publisher (Colorado State University. Libraries, 2003)
The development of hydraulics and fluid mechanics at Colorado State University is reviewed in reference to those who pioneered the analysis of hydraulic and wind engineering. The article will first cover the "early developments" with Elwood Meade, Charles Lory, Ralph Parshall and Emory Lane during the Colorado A&M period. The name change to Colorado State University initiated considerable expansion through fruitful collaboration with the USGS and the USBR. The "expansion years" featured the contributions of Maury Albertson, Hunter Rouse, Jack Cermak and Everett Richardson with direct administrative support from Lionel Baldwin, Daryl Simons and Ray Chamberlain. The more recent "mature period" saw broadening of the programs and expansion into environmental engineering. The emphasis of the article will be on the historical contribution of CSU to hydraulics and fluid mechanics. Some of the key scientific achievements will be reviewed. There will be a brief documentation of the interaction between faculty activities, academic programs and research facilities that led to rapid growth and development. The success and visibility of the programs also hinged on several other factors including significant contributions at the international level through projects in Pakistan (Tarbela Dam) and Egypt.
Hydrology days 2003
AGU hydrology days 2003
23rd annual AGU hydrology days was held on March 31 - April 2, 2003 at Colorado State University.